La Armada Imperial Japonesa en México: ¿búsqueda de una alianza militar o despliegue de estrategias geopolíticas? - Uscanga, Carlos (El Colegio de México, 2021)
The first decades of the twentieth century marked the rise of political and diplomatic tensions between Japan and the United States. The increased friction reflected a geostrategic positioning in which Latin America was center stage and Mexico played an important role by implementing actions to capitalize on Japan’s overtures. In this particular context, the press and U.S. intelligence services frequently referred to a “military treaty” between Mexico and Japan. The actions of the Japanese Imperial Navy were also influential in the period leading up to the outbreak of the War of the Pacific on 7 December 1941.